Pengaruh Perbedaan Mesh Terstruktur dan Mesh Tidak Terstruktur Pada Simulasi Sistem Pendinginan Mold Injeksi Produk Plastik - Bagus Prasetiyo, Angger; Fauzun,; Azhim Asyratul Azmi,; Didit Setyo Pamuji,; Rizqi Ilmal Yaqin, (ReTII, 2019)
Determination of the type of mesh and mesh manufacturing density plays a very important role in a simulation, this is due to minimize the time and computational costs. This study presents a comparison of the influence of mesh on CFD analysis. Mesh is the most important part in doing a simulation. Mesh is good, affects the calculation results of a simulation. To simulate internal flow in injection molding cooling channels to make it more accurate. There are three types of mesh that are applied in a simulation of this study, namely: hexahedral, polyhedral, and tetrahedral mesh are applied to simulate the internal flow of cooling channel injection molding using the k-epsilon turbulence model. Simulation results show that the simulation method using the polyhedral mesh is proposed to be able to speed up calculations and accelerate the convergence of the simulation as evidenced by an iteration graph. The use of polyhedral mesh in CFD simulations is more effective than using tetrahedral or hexahedral mesh. However, the use of hexahedral mesh simulation results is closer to the experiment and requires a long iteration time. In addition, the result is polyhedral mesh requires less computational time than hexahedral mesh and tetrahedral mesh. Using polyhedral mesh in CFD was found to be more effective than using tetrahedral elements.